Evaluation of Trauma Triage Criteria Performance in a Regional Trauma System. (2nd November 2019) - Bosson, Nichole; Kaji, Amy H.; Gausche-Hill, Marianne; Kim, Dennis; Putnam, Brant; Schlesinger, Shira; Singer, George; Lewis, Roger J.
Abstract: Objective: We evaluated the performance of individual trauma triage criteria using data from a regional trauma registry. Methods: Los Angeles County (LAC) paramedics use triage criteria adapted from the 2011 Center for Disease Control (CDC) guidelines to triage injured patients to Trauma Centers (TCs). TCs report outcomes to a LAC EMS registry. We abstracted data for patients 15 years or older from 2013 to 2015 and identified all trauma triage criteria that were met for each encounter. Study outcomes were: (1) "clear need" for a TC, defined as receiving a non-orthopedic operative intervention within 6 hours of arrival, injury severity score (ISS) > 15, or surgical ICU admission; or (2) "no need" for a TC, defined as discharge home from the emergency department (ED). We also defined "possible need" as those patients not discharged home from the ED, inclusive of "clear need" and all other admitted patients. For each individual triage criteria, we calculated the positive likelihood ratios and positive predictive values for TC need. Results: There were 71, 536 adult patients in the registry transported by EMS to a LAC TC during the study. Median age was 38 years (IQR 25–55) with 73% male. There were 23, 628 (33%) who met "no need" criteria for a TC, leaving 47, 908 (67%) patients with "possible need" for a TC, of whom 13, 343 patients (19% of total) met "clear need" for a TC. No individual trauma criterion met the a priori likelihood ratio threshold of 10 for predicting "clear need" for a TC. Cardiopulmonary arrest with penetrating torso trauma and flail chest met this threshold for "possible need." Conclusion: In this retrospective analysis, no individual triage criterion definitively identified patients who benefit from transport to a TC. Yet, the majority of patients demonstrated potential benefit for nearly all criteria, supporting CDC recommendations that trauma triage criteria be considered in their entirety, not as individual criterion.